Catchy and conversational? A register analysis of pop lyrics. Issue 2 (August 2021) - Werner, Valentin
Abstract : This study presents a register analysis of pop lyrics. To this end, it applies multi-dimensional register analysis to empirically test claims regarding the allegedly conversational nature of pop lyrics. It thus follows broader calls for the linguistic exploration of performed language as represented in non-canonical pop culture registers. This text-linguistic investigation relies on a corpus of contemporary pop lyrics and uses the Multidimensional Analysis Tagger (Nini, 2018 ), software that replicates Biber's (1988) tagger, to identify register features to contrast lyrics with other varieties of text. In addition, the n -gram and keyword functionalities of a concordancer are used for establishing register markers and style features to identify characteristic properties of pop lyrics. In line with earlier claims, it becomes apparent that pop lyrics indeed carry some conversational force despite situational factors being indicative of planned and performed production. Furthermore, this analysis identifies additional features that are highly distinctive of pop lyrics ( versus general conversation), and is suggestive of the special status of this register on the speech-writing continuum.